A polyurethane / conductive carbon black composite foam flexible sensor and a preparation method thereof

CN117801352BActive Publication Date: 2026-10-30QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311842696.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-30
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

但通常需要借助特定溶剂或繁杂的工艺过程不符合绿色环保大趋势

Benefits of technology

[0025](1)本发明采用低成本的导电炭黑作为导电填料,避免了碳纳米管、石墨烯等高成本导电填料的使用,显著降低了原料成本;并通过行星式共混装置结合聚乙烯醇水溶液进行发泡,有效克服了导电炭黑在引入聚氨酯发泡体系的过程中,难以有效添加和高效分散的技术难题,构建了具有厚壁泡孔特征,导电炭黑在泡壁中实现纳米分散的独特微观泡沫结构,展现出独特的正压阻效应和优良的力学强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117801352B_ABST
    Figure CN117801352B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of new materials, and relates to a polyurethane / conductive carbon black composite foam flexible sensor and a preparation method. Pure water is used for foaming, polyvinyl alcohol aqueous solution and a planetary blending device are used for double dispersion, and high-water-content waterborne polyurethane prepolymer is used for mixing and foaming, and then drying is performed to obtain high-strength, positive pressure resistance polyurethane / conductive carbon black composite foam. Conductive carbon black is selected as a conductive filler to form a conductive path with a positive pressure resistance effect in a polyurethane foam matrix, so that the composite foam has high compressive strength and flexible characteristics of being bendable. The composite foam has excellent piezoresistive detection sensitivity in a very wide detection range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new materials technology and relates to a flexible polyurethane / conductive carbon black composite foam sensor and its preparation method. Background Technology

[0002] Since the beginning of the 21st century, the rapid development of artificial intelligence and wireless communication has driven the demand for portable electronic devices, leading to widespread attention on the development and application of flexible sensors. Currently, different pressure sensing mechanisms have been developed based on their working principles, such as piezoelectric, capacitive, and piezoresistive sensors. Among these, piezoresistive pressure sensors stand out due to their simple structure, direct readout mechanism, and low power consumption, and are widely used in health monitoring, wearable electronic devices, and intelligent robots. Furthermore, compared to metal-based and semiconductor-based sensors, the use of conductive fillers combined with polymers to create piezoresistive conductive polymer sensors imparts lightweight and flexibility, making it a superior choice for pressure sensors. In recent years, to meet the application needs of more fields, it is necessary to improve the sensitivity and detection upper limit of piezoresistive devices, which essentially means improving the sensing capability of materials under high loads. However, it has also been found that most existing piezoresistive sensors exhibit negative piezoresistive behavior (i.e., resistance decreases with increasing pressure). The absolute value of the sensor's resistance change ΔR / R0 = (R-R0) / R0 (where R and R0 are the resistances under applied and unapplied pressure, respectively) is always less than 100%, theoretically limiting the sensor's sensitivity and detection limit. Therefore, the development and application of high-strength sensor devices with positive piezoresistive properties (resistance increases with increasing pressure) are of great significance for improving sensitivity and raising the upper limit of load capacity.

[0003] Currently, the most common method is to obtain flexible piezoresistive sensing materials by using conductive fillers (metal particles such as silver or gold nanoparticles, carbon black (CB), carbon nanotubes (CNT), carbon nanofibers (CNC), graphene (GO), etc.) through impregnation, sacrificial template methods, induced phase separation, supercritical foaming, etc. While foam materials obtained using impregnation processes exhibit excellent performance, the conductive fillers coated on the surface often exhibit a negative piezoresistive effect through the "contact effect," resulting in low sensitivity and exceeding the detection limit under large strain or high stress. Furthermore, due to the rigidity and brittleness of the conductive fillers, poor integration with the matrix leads to problems such as flaking and defects after prolonged use. On the other hand, the impregnated foam substrate often limits the improvement of mechanical strength, further restricting the detection range of composite sensing materials. Dispersing conductive fillers into a polymer matrix through 3D printing, supercritical foaming, etc., to generate piezoresistive behavior can improve the compressive strength of the matrix, which is an effective way to improve the load-bearing capacity of piezoresistive materials. However, this usually requires specific solvents or complex processes, which is inconsistent with the trend towards green and environmentally friendly practices. Therefore, it is of great significance to develop a simple and green synthesis process to achieve piezoresistive sensing with a wide detection range and high detection sensitivity. Summary of the Invention

[0004] To address the aforementioned problems, this invention aims to prepare a flexible conductive foam with high strength and positive piezoresistive properties. It utilizes conductive carbon black to construct a positive piezoresistive conductive path, designing a polyurethane / conductive carbon black composite foam flexible sensor with a wide detection range, high detection sensitivity, and positive piezoresistive effect. The technical solution includes: foaming with pure water, using a dual dispersion effect of polyvinyl alcohol aqueous solution and a planetary blending device, mixing and foaming with a high-water-capacity aqueous polyurethane prepolymer, and drying to obtain a high-strength, positive piezoresistive polyurethane / conductive carbon black composite foam. This invention selects conductive carbon black as a conductive filler to form a conductive path with a positive piezoresistive effect within the polyurethane foam matrix, thereby enabling the composite foam to acquire excellent mechanical and electrical properties.

[0005] To achieve the above objectives, the present invention provides a method for preparing a flexible polyurethane / conductive carbon black composite foam sensor, comprising the following steps:

[0006] (1) Dissolve polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol aqueous solution;

[0007] (2) After mixing the dehydrated polyol, polyisocyanate and small molecule chain extender, a prepolymer is obtained. Then, a delayed catalyst is added to obtain an aqueous polyurethane prepolymer.

[0008] (3) The polyvinyl alcohol aqueous solution in step (1), the waterborne polyurethane prepolymer in step (2) and the conductive filler are mixed and foamed in a planetary mixing device, and then the excess water is removed by drying to obtain polyurethane / conductive carbon black composite foam.

[0009] (4) Cut the polyurethane / conductive carbon black composite foam described in step (3) into block samples, coat the upper and lower surfaces of the samples with conductive silver paste and then adhere copper foil, and cure at room temperature to obtain the polyurethane / conductive carbon black composite foam sensor.

[0010] Preferably, the polyvinyl alcohol in step (1) is polyvinyl alcohol 1750 or polyvinyl alcohol 1799.

[0011] More preferably, the mass ratio of polyvinyl alcohol to deionized water in step (1) is (0.5-1.5):10.

[0012] Preferably, in step (2): the dehydrated polyol, polyisocyanate and small molecule chain extender are mixed and stirred at 80°C for 4 hours to obtain a prepolymer. After cooling, a delay catalyst is added to obtain an aqueous polyurethane prepolymer.

[0013] Preferably, the polyol in step (2) is polyethylene glycol; the number average molecular weight of the polyethylene glycol is 950-1050, and the hydroxyl value of the polyethylene glycol is 107-118.

[0014] Preferably, the polyisocyanate in step (2) is selected from at least one of toluene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate.

[0015] Preferably, the small molecule chain extender in step (2) is trimethylolpropane; and the delayed catalyst is DabcoBL-17.

[0016] More preferably, the molar ratio of trimethylolpropane to polyol is 1:3.

[0017] More preferably, the mass ratio of Dabco BL-17 to the prepolymer is 1:250.

[0018] Preferably, in step (2), the molar ratio of the hydroxyl groups in the polyol to the isocyanate groups in the polyisocyanate is 1:2.

[0019] Preferably, the conductive filler in step (3) is conductive carbon black. The conductive filler is preferably a conductive filler with low density and large volume.

[0020] More preferably, the mass ratio of the polyvinyl alcohol aqueous solution to the aqueous polyurethane prepolymer and the conductive carbon black is (2.1-2.3):1:(0.15-0.35).

[0021] Preferably, in step (3), the planetary mixer rotates at 1500-2000 rpm for 130-140 seconds.

[0022] Preferably, the drying in step (3) is freeze drying, which is carried out at -70 to -50°C for 40-48 hours.

[0023] The present invention also provides a flexible polyurethane / conductive carbon black composite foam sensor prepared by the above method.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] (1) This invention uses low-cost conductive carbon black as a conductive filler, avoiding the use of high-cost conductive fillers such as carbon nanotubes and graphene, and significantly reducing the cost of raw materials; and by using a planetary blending device combined with polyvinyl alcohol aqueous solution for foaming, it effectively overcomes the technical problem of difficult addition and efficient dispersion of conductive carbon black in the process of introducing it into the polyurethane foaming system, and constructs a unique micro foam structure with thick-walled cell characteristics, in which conductive carbon black is nano-dispersed in the cell wall, exhibiting a unique positive piezoresistive effect and excellent mechanical strength.

[0026] (2) The polyurethane / conductive carbon black composite foam flexible sensor prepared by the present invention has an extremely wide pressure detection range, covering a pressure detection range from 0 kPa to 2840 kPa.

[0027] (3) The polyurethane / conductive carbon black composite foam flexible sensor prepared by this invention has extremely high piezoresistive detection sensitivity, with a strain sensitivity gain value (GF) as high as 211 (when the compressive strain is higher than 35%), far exceeding that of previous piezoresistive sensors (GF values ​​are basically below 100). Even at low compressive strain (strain below 35%), GF exhibits extremely high values ​​(GF = 2.88 for strains below 6%; GF is between 19.61 and 70.23 for strains from 6% to 35%), far exceeding similar products. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the polyurethane / conductive carbon black composite foam preparation process of the present invention.

[0029] Figure 2 The image shows the composite material after foaming but before freeze-drying in step (3) of Embodiment 1 of the present invention; a is an appearance view; b is a cross-sectional view.

[0030] Figure 3 This is a bending diagram of the composite foam sample prepared in Example 1 of the present invention.

[0031] Figure 4 This is a microscopic morphology diagram of the composite foam prepared in Example 1 of the present invention.

[0032] Figure 5This is a schematic diagram of the fabrication process of the polyurethane / conductive carbon black composite foam sensor of the present invention.

[0033] Figure 6 This is a schematic diagram showing the resistivity and conductivity of the polyurethane / conductive carbon black composite foam prepared in Examples 1-3 of the present invention.

[0034] Figure 7 The stress and resistance change response curves of the polyurethane / conductive carbon black composite foam strain sensor prepared in Example 1 of this invention are shown.

[0035] Figure 8 This is a schematic diagram of the cyclic piezoresistive effect of the polyurethane / conductive carbon black composite foam strain sensor of the present invention under high intensity.

[0036] Figure 9 This is a microscopic morphology diagram of the foam obtained in Comparative Example 1.

[0037] Figure 10 The images show the appearance and microscopic views of the composite foams of Example 1 and Comparative Example 2. Detailed Implementation

[0038] The present invention will be further described below with reference to specific embodiments, and the advantages and features of the present invention will become clearer with the description. However, the embodiments are merely exemplary and do not constitute any limitation on the scope of the present invention. Those skilled in the art should understand that modifications or substitutions can be made to the details and form of the technical solutions of the present invention without departing from the spirit and scope of the present invention, but all such modifications and substitutions fall within the protection scope of the present invention.

[0039] Example 1

[0040] A method for fabricating a flexible polyurethane / conductive carbon black composite foam sensor, see [link to documentation]. Figure 1 The preparation process includes the following steps:

[0041] (1) Weigh 1.0g of polyvinyl alcohol 1799 and dissolve it in 10g of deionized water at 105℃ to prepare a 1:10 polyvinyl alcohol aqueous solution, which is then kept for later use.

[0042] (2) Take 30g of dried polyethylene glycol (number average molecular weight of 1000; hydroxyl value of 112.2, and the amount of hydroxyl group of polyethylene glycol is 0.06mol), 10.45g of 1,6-hexamethylene diisocyanate (the amount of isocyanate group is 0.12mol) and trimethylolpropane (1.33g, the amount of substance is 0.01mol) and add them to the reaction vessel. React for 4h under mechanical stirring at 200rpm and 80℃ to obtain a prepolymer. After cooling, add 0.4g of DabcoBL-17 per 100g of prepolymer to obtain an aqueous polyurethane prepolymer.

[0043] (3) Take 11.0g of the polyvinyl alcohol aqueous solution obtained in step (1), 1g of conductive carbon black, and 5g of waterborne polyurethane prepolymer and place them in a mold. Then, place the mold in a planetary mixer and mix and foam at 2000rpm for 140s. The resulting material is as follows: Figure 2 As shown in the figure; then, excess moisture was removed by freeze drying (-70℃, <10Pa, 48h) to obtain polyurethane / conductive carbon black composite foam. Figure 3 The foam slice sample shown is bendable. Its microstructure (SEM) is as follows: Figure 4 As shown in Figure (a), this method can effectively obtain thick-walled foams with uniform pore size, with pore diameter and wall thickness distributed around 60 μm and 50 μm, respectively. This structure is beneficial for improving its mechanical strength. Further magnification, Figure (c) clearly shows the embedded carbon black particles, indicating good dispersion.

[0044] The resistivity and conductivity of the polyurethane / conductive carbon black composite foam obtained in this step were measured, and the results are as follows: Figure 6 As shown in the image.

[0045] (4) According to Figure 5 The sensor is prepared by cutting the polyurethane / conductive carbon black composite foam described in step (3) into block samples, coating the upper and lower surfaces of the samples with conductive silver paste and then adhering copper foil, and curing at room temperature to obtain a high-strength, positive piezoresistive polyurethane / conductive carbon black composite foam sensor.

[0046] The stress and resistance changes of the above-mentioned polyurethane / conductive carbon black composite foam sensor after compression are as follows: Figure 7 As shown in the figure, the foam sensor exhibits typical positive piezoresistive behavior, meaning the resistance gradually increases with increasing compression. At 50% compressive strain, the stress reaches a high of 2840 kPa, demonstrating an extremely wide detection range. Correspondingly, the strain sensitivity gain value GF (gauge factor, (ΔR / R0) / strain) can be obtained from the figure. Specifically, below 6% strain, GF = 2.88; from 6% to 35% strain, GF ranges from 19.61 to 70.23; and above 35% strain, GF reaches 211. This demonstrates extremely high strain piezoresistive sensitivity.

[0047] The cyclic piezoresistive strength of the above polyurethane / conductive carbon black composite foam sensor at 500 kPa was measured as follows: Figure 8 As shown in the figure, this sensor can exhibit excellent response at higher pressures and is expected to be applied to a wider range of sensing fields.

[0048] Example 2

[0049] A method for fabricating a flexible polyurethane / conductive carbon black composite foam sensor, see [link to documentation]. Figure 1 The preparation process includes the following steps:

[0050] (1) Weigh 1.0g of polyvinyl alcohol 1799 and dissolve it in 10g of deionized water at 105℃ to prepare a 1:10 polyvinyl alcohol aqueous solution, which is then kept for later use.

[0051] (2) Take 30g of dried polyethylene glycol (number average molecular weight of 1000; hydroxyl value of 112.2, and the amount of hydroxyl group of polyethylene glycol is 0.06mol), 10.45g of 1,6-hexamethylene diisocyanate (the amount of isocyanate group is 0.12mol) and trimethylolpropane (1.33g, the amount of substance is 0.01mol) and add them to the reaction vessel. React for 4h under mechanical stirring at 200rpm and 80℃. After cooling, add 0.4g of DabcoBL-17 per 100g of prepolymer to obtain waterborne polyurethane prepolymer.

[0052] (3) Take 11.0g of the polyvinyl alcohol aqueous solution, 0.75g of conductive carbon black and 5g of waterborne polyurethane prepolymer obtained in step (1) and place them in a mold. Place the mold in a planetary mixing device and mix and foam at 2000rpm for 140s. Then remove excess water by freeze drying to obtain polyurethane / conductive carbon black composite foam.

[0053] The resistivity and conductivity of the polyurethane / conductive carbon black composite foam obtained in this step were measured, and the results are as follows: Figure 6 As shown in the image.

[0054] (4) Cut the polyurethane / conductive carbon black composite foam described in step (3) into block samples, coat the upper and lower surfaces of the samples with conductive silver paste and then adhere copper foil, and cure at room temperature to obtain a high-strength, positive piezoresistive polyurethane / conductive carbon black composite foam sensor.

[0055] Example 3

[0056] A method for fabricating a flexible polyurethane / conductive carbon black composite foam sensor, see [link to documentation]. Figure 1 The preparation process includes the following steps:

[0057] (1) Weigh 1.0g of polyvinyl alcohol 1799 and dissolve it in 10g of deionized water at 105℃ to prepare a 1:10 polyvinyl alcohol aqueous solution, which is then kept for later use.

[0058] (2) Take 30g of dried polyethylene glycol (number average molecular weight of 1000; hydroxyl value of 112.2, and the amount of hydroxyl group of polyethylene glycol is 0.06mol), 10.45g of 1,6-hexamethylene diisocyanate (the amount of isocyanate group is 0.12mol) and trimethylolpropane (1.33g, the amount of substance is 0.01mol) and add them to the reaction vessel. React for 4h under mechanical stirring at 200rpm and 80℃. After cooling, add 0.4g of DabcoBL-17 per 100g of prepolymer to obtain waterborne polyurethane prepolymer.

[0059] (3) Take 11.0g of the polyvinyl alcohol aqueous solution, 1.25g of conductive carbon black and 5g of waterborne polyurethane prepolymer obtained in step (1) and place them in a mold. Place the mold in a planetary mixing device and mix and foam at 2000rpm for 140s. Then remove excess water by freeze drying to obtain polyurethane / conductive carbon black composite foam.

[0060] The resistivity and conductivity of the polyurethane / conductive carbon black composite foam obtained in this step were measured, and the results are as follows: Figure 6 As shown in the image.

[0061] (4) Cut the polyurethane / conductive carbon black composite foam described in step (3) into block samples, coat the upper and lower surfaces of the samples with conductive silver paste and then adhere copper foil, and cure at room temperature to obtain a high-strength, positive piezoresistive polyurethane / conductive carbon black composite foam sensor.

[0062] Comparative Example 1

[0063] A method for preparing polyurethane / conductive carbon black composite foam, see [link to relevant documentation]. Figure 1 The preparation process includes the following steps:

[0064] (1) Weigh out 10g of deionized water for later use.

[0065] (2) Take 30g of dried polyethylene glycol (number average molecular weight of 1000; hydroxyl value of 112.2, and the amount of hydroxyl group of polyethylene glycol is calculated to be 0.06mol), 10.45g of 1,6-hexamethylene diisocyanate (the amount of isocyanate group calculated to be 0.12mol) and trimethylolpropane (1.33g, the amount of substance is 0.01mol) and add them to the reaction vessel. React for 4h under mechanical stirring at 200rpm and 80℃. After cooling, add 0.4g of DabcoBL-17 per 100g of prepolymer to obtain waterborne polyurethane prepolymer.

[0066] (3) Take 10g of deionized water, 1g of conductive carbon black and 5g of waterborne polyurethane prepolymer from step (1) and place them in a mold. Place the mold in a planetary mixing device and mix and foam at 2000rpm for 140s. Then remove excess water by freeze drying to obtain polyurethane / conductive carbon black composite foam.

[0067] (4) Cut the polyurethane / carbon black conductive foam described in step (3) into block samples.

[0068] The foam obtained in this step is characterized by its morphology. Figure 9 The image shows the microstructure of the foam. It indicates that the pores are uneven and few in number, which is detrimental to the flexibility of the foam, and the conductive carbon black is in an aggregated state without effective dispersion.

[0069] Comparative Example 2

[0070] A method for preparing polyurethane / conductive carbon black composite foam includes the following steps:

[0071] (1) Weigh 1.0g of polyvinyl alcohol and dissolve it in 10g of deionized water at 105℃ to prepare a 1:10 polyvinyl alcohol aqueous solution, which is then kept for later use.

[0072] (2) Take 30g of dried polyethylene glycol (number average molecular weight of 1000; hydroxyl value of 112.2, and the amount of hydroxyl group of polyethylene glycol is 0.06mol), 10.45g of 1,6-hexamethylene diisocyanate (the amount of isocyanate group is 0.12mol) and trimethylolpropane (1.33g, the amount of substance is 0.01mol) and add them to the reaction vessel. React for 4h under mechanical stirring at 200rpm and 80℃. After cooling, add 0.4g of DabcoBL-17 per 100g of prepolymer to obtain waterborne polyurethane prepolymer.

[0073] (3) Take 11.0g of the polyvinyl alcohol aqueous solution, 1.0g of conductive carbon black and 5g of waterborne polyurethane prepolymer obtained in step (1) and place them in a mold. Perform conventional mechanical stirring at a speed of 2000rpm. After stirring for 60s, allow it to foam freely. Then remove excess water by freeze drying to obtain polyurethane / conductive carbon black composite foam.

[0074] (4) Cut the polyurethane / conductive carbon black composite foam described in step (3) into block samples.

[0075] The appearance and microstructure of the foam obtained in this step were characterized. The results are as follows: Figure 10 As shown, compared with planetary mixing, conventional mechanical mixing produces a loose foam structure that cannot achieve high strength properties.

Claims

1. A method for preparing a flexible polyurethane / conductive carbon black composite foam sensor, characterized in that, Includes the following steps: (1) Dissolve polyvinyl alcohol in deionized water to obtain a polyvinyl alcohol aqueous solution; (2) The dehydrated polyol, polyisocyanate and small molecule chain extender are mixed and reacted to obtain a prepolymer, and then a delayed catalyst is added to obtain an aqueous polyurethane prepolymer; wherein, the molar ratio of hydroxyl groups in the polyol to isocyanate groups in the polyisocyanate is 1:

2. (3) The polyvinyl alcohol aqueous solution described in step (1), the aqueous polyurethane prepolymer described in step (2), and the conductive carbon black are mixed and foamed in a planetary mixing device, and then excess water is removed by drying to obtain polyurethane / conductive carbon black composite foam; wherein, the mass ratio of polyvinyl alcohol aqueous solution to aqueous polyurethane prepolymer and conductive carbon black is (2.1~2.3):1: (0.15~0.35); (4) Cut the polyurethane / conductive carbon black composite foam described in step (3) into block samples, coat the upper and lower surfaces of the samples with conductive silver paste and then adhere copper foil, and cure at room temperature to obtain the polyurethane / conductive carbon black composite foam sensor.

2. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The polyvinyl alcohol mentioned in step (1) is polyvinyl alcohol 1750 or polyvinyl alcohol 1799.

3. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The mass ratio of polyvinyl alcohol to deionized water in step (1) is (0.05~0.15):

1.

4. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, Step (2): After mixing the dehydrated polyol, polyisocyanate and small molecule chain extender, stir and react at 80°C for 4 hours to obtain a prepolymer. After cooling, add a delayed catalyst to obtain an aqueous polyurethane prepolymer.

5. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The polyol mentioned in step (2) is polyethylene glycol; the number average molecular weight of the polyethylene glycol is 950-1050, and the hydroxyl value of the polyethylene glycol is 107-118.

6. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The polyisocyanate mentioned in step (2) is selected from at least one of toluene diisocyanate, isophorone diisocyanate, 1,6-hexamethylene diisocyanate, and dicyclohexylmethane diisocyanate.

7. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The small molecule chain extender mentioned in step (2) is trimethylolpropane; the delayed catalyst is Dabco BL-17.

8. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 7, characterized in that, The molar ratio of trimethylolpropane to polyol is 1:

3.

9. A method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 7, characterized in that, The mass ratio of Dabco BL-17 to the prepolymer is 1:

250.

10. A method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, In step (3), the planetary mixer rotates at 1500-2000 rpm for 130-140 s.

11. The method for preparing a polyurethane / conductive carbon black composite foam flexible sensor according to claim 1, characterized in that, The drying process described in step (3) involves freeze-drying at -70 to -50°C for 40 to 48 hours.

12. The polyurethane / conductive carbon black composite foam flexible sensor prepared by the method according to any one of claims 1-11.

Citation Information

Patent Citations

  • Dispersant and resin composition

    JP2021115523A